New shell information and new generic attributions for the Egyptian podocnemidid turtles “Podocnemis” fajumensis (Oligocene) and “Podocnemis” aegyptiaca (Miocene) - A. Pérez-García (Fossil Record, 2021)
The early Oligocene “Podocnemis” fajumensis and the early Miocene “Podocnemis” aegyptiaca are two podocnemidid turtles from northern Egypt, defined more than a century ago. Their identification as representatives of the South American genus Podocnemis cannot currently be supported. Relatively limited information on both species was available. In fact, no photograph on the shell of either of them has been published so far, and the type material of both is currently lost. Shell remains of almost 15 specimens of “Podocnemis” fajumensis are analyzed here, including a complete carapace and two complete plastra. A neotype is designated here for the species. An artificial mold of the holotype of “Podocnemis” aegyptiaca is identified, corresponding to its holoplastotype. Both “Podocnemis” fajumensis and “Podocnemis” aegyptiaca are confirmed as valid species, attributable to Erymnochelyini, a clade currently exclusively represented by the Malagasy Erymnochelys madagascariensis. A new diagnosis is proposed for each of these extinct species, including both autapomorphies and a unique combination of characters. They are attributed to two new genera, corresponding to the oldest defined for the African record of Erymnochelyini. Thus, the new combinations Shetwemys fajumensis (http://zoobank.org/NomenclaturalActs/B4805343-8533-4DA7-808B-BB972D4471CB, urn:lsid:zoobank.org:act:B4805343-8533-4DA7-808B-BB972D4471CB) and Apeshemys aegyptiaca (http://zoobank.org/NomenclaturalActs/43DD73CF-AAED-47A0-9FFB-EB6CFB80D389, urn:lsid:zoobank.org:act:43DD73CF-AAED-47A0-9FFB-EB6CFB80D389) are proposed.